Proline Biosynthesis Enzyme Genes Confer Salt Tolerance to Switchgrass (Panicum virgatum L.) in Cooperation With Polyamines Metabolism - Guan, Cong; Cui, Xin; Liu, Hua-yue; Li, Xue; Li, Meng-qi; Zhang, Yun-wei (Frontiers in Plant Science, 2020)
Understanding the regulation of proline metabolism necessitates the suppression of two Δ1-pyrroline-5-carboxylate synthetase enzyme (P5CS) genes performed in switchgrass (Panicum virgatum L.). The results reveal that overexpressing PvP5CS1 and PvP5CS2 increased salt tolerance. Additionally, transcript levels of spermidine (Spd) and spermine (Spm) synthesis and metabolism related genes were upregulated in PvP5CS OE-transgenic plants and downregulated in the PvP5CS RNAi transformants. According to salt stress assay and the measurement of transcript levels of Polyamines (PAs) metabolism-related genes, P5CS enzyme may not only be the key regulator of proline biosynthesis in switchgrass, but it may also indirectly affect the entire subset of pathway for ornithine to proline or to putrescine (Put). Furthermore, application of proline prompted expression levels of Spd and Spm synthesis and metabolism-related genes in both PvP5CS-RNAi and WT plants, but transcript levels were even lower in PvP5CS-RNAi compared to WT plants under salt stress condition. These results suggested that exogenous proline could accelerate polyamines metabolisms under salt stress. Nevertheless, the enzymes involved in this process and the potential functions remain poorly understood. Thus, the aim of this study is to reveal how proline functions with PAs metabolism under salt stress in switchgrass.